2017
DOI: 10.1177/2047487317747498
|View full text |Cite
|
Sign up to set email alerts
|

Higher pulse pressure and risk for cardiovascular events in patients with essential hypertension: The Campania Salute Network

Abstract: Background Increased pulse pressure is associated with structural target organ damage, especially in elderly patients, increasing cardiovascular risk. Design In this analysis, we investigated whether high pulse pressure retains a prognostic effect also when common markers of target organ damage are taken into account. Methods We analysed an unselected cohort of treated hypertensive patients from the Campania Salute Network registry ( n = 7336). Participants with available cardiac and carotid ultrasound were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 43 publications
5
40
0
Order By: Relevance
“…Importantly, such studies should also take potential nonlinear relationships into account, as the effects of hypo-and hyperthyroidism on blood pressure come together within the normal range. This is important, as observational studies have shown that increased pulse pressure is an independent predictor of cardiovascular events in patients with hypertension (59,60), as well as a predictor for peripheral arterial disease (61).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, such studies should also take potential nonlinear relationships into account, as the effects of hypo-and hyperthyroidism on blood pressure come together within the normal range. This is important, as observational studies have shown that increased pulse pressure is an independent predictor of cardiovascular events in patients with hypertension (59,60), as well as a predictor for peripheral arterial disease (61).…”
Section: Discussionmentioning
confidence: 99%
“…This largely agrees with our results regarding increased CV events (myocardial infarction, stroke, heart failure). Similar findings were reported by the previous investigation …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elevated PP can be used as a functional marker of target organ damage. 13 The study by Selvaraj et al 14 provided robust evidence on the role of PP in cardiovascular risk outcomes. However, when the predictive value of a 10-mmHg increase in PP was evaluated, a protective effect of elevated PP was found.…”
Section: Journal Of Transcatheter Interventionsmentioning
confidence: 99%